The emerging therapy with probiotics in the management of inflammatory bowel disease: current status - Kumar, Rajiv; Singh, Jagjit (International Journal of Basic & Clinical Pharmacology, 2017)
Inflammatory Bowel Disease (IBD) comprises Ulcerative Colitis (UC) and Crohn’s Disease (CD) with unknown aetiology. Most of the drugs used to treat IBD as standard treatment produce adverse effects during long term therapy. Evidence has suggested a role of intestinal microbiota in IBD. The use of probiotics and prebiotics is the natural approach to treat IBD. The objective of this article was to review the studies on probiotics that cover the therapeutic status in Inflammatory Bowel Disease. Appraisal of published articles from peer reviewed journals, search from PubMed and Wiley Blackwell website for English language publications using defined key words according to disease type. Studies have shown that probiotic agents play an important role in IBD and these are VSL#3, Bifido-ferminted milk, Escherichia coli Nissle 1917, Saccharomyces boulardi and “BIO-THREE for inducing remission in patients with active UC, for preventing relapses in inactive UC patients and also in UC patients with ileo-anal pouch anastomosis. Lactobacillllus rhamnosus GG and Lactobacillllus johnsonii LA1 can prevent endoscopic recurrences in patients with inactive CD. Probiotic intervention study designs in IBD patients searched were RCT vs Placebo / RCT vs standard treatment . Studies - with uncontrolled design, - with prebiotics intervention and with helminths were also searched. There is a promising role of probiotics and prebiotics in chronic mucosal inflammation that occurs in Inflammatory Bowel Disease. Sufficient evidence to support the role of probiotics in CD are not available. Well designed RCT studies based on intention -to- treat analyses are required.